Some Peculiarities of Establishing the Legal Status of Military Volunteers in the EAEU and BRICS Member States - D. А. Semiannikova (Евразийская интеграция: экономика, право, политика, 2024)
The article deals with the peculiarities of legal regulation in the EAEU and BRICS member countries, enshrining the status of volunteers who joined the armed forces of the state, the procedure and conditions of such participation and participation in armed (military) conflicts on behalf of the state. Aim. The purpose of the article is to study the legal regulation in the EAEU and BRICS member countries defining the status of volunteers who joined the armed forces of the state.Tasks. To characterize and identify the peculiarities of the legal status of persons participating in volunteer formations of the armed forces of the EAEU and BRICS member countries. To consider the new for modern Russia legal regulation that established the status of volunteers participating in a special military operation.Method. In the process of the research the set tasks were solved by the author with the use of general scientific (historical, dialectical, systematic, logical, method of analysis) and legal (comparative-legal, sociological, axiological) methods of research.Results. In most countries, the establishment of the legal status of a volunteer, including social guarantees, depends directly on the country’s involvement in a particular armed conflict or external threats that result in the need for the state to strengthen its military power and, consequently, for persons to volunteer for military service. Armenia and Russia are prime examples of such countries. Over the past two years, Russian legislation has gone a long way towards defining the legal status of volunteers.Conclusions. Analyzing the legal regulation enshrining the legal status of volunteers of the armed forces of the countries under study, it is necessary to note several directions. Thus, in fact, in all BRICS and EAEU member countries considered in the study, the participation of volunteers in the armed forces is regulated by legislation. The only country whose legislation does not provide for the participation of volunteers in the country’s armed forces is the BRICS member country South Africa. In analyzing the legal regulation of the EAEU member countries, it should be noted that the legislation of these countries has similar features. At the same time, the level of provision by the state of this category of citizens varies from its absence, as in India, to the provision by the state to volunteers of all social guarantees and equalization of their status with military personnel, as in China and Russia.